ANALYSIS OF THE QUALITY OF GRAIN AGRICULTURAL PRODUCTS OF KHMELNYTSKYI REGION - TKACHUK, HANNA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The demand for specialists in the field of chemistry and chemical engineering capable of solving applied management tasks at industry enterprises with the aim of developing environmental protection chemical technologies became the reason for starting the training of such specialists within the walls of the Khmelnytskyi National University (KhNU). Educational program (ЕP) Chemical technologies and engineering is the only one for this specialty in Khmelnytskyi region, therefore the industry and regional contexts are the basis of the goal and objectives of training specialists in chemical technologies. One of the mandatory components of the master's training in chemical technologies and engineering is "Quality of raw materials and products of chemical technologies". As you know, the lion's share of industrial production in our country is the production and processing of agricultural products, and Khmelnytskyi region is traditionally one of the leaders in the production of grain crops throughout Ukraine. The following factors affect the quality of grain in the Khmelnytskyi region. A wide range of varieties of grain crops adapted to local conditions are grown in the region. Modern growing technologies, use of fertilizers and plant protection products contribute to obtaining high-quality grain. A favorable climate contributes to the accumulation of nutrients in grain. Fertile soils of the region ensure high yield and quality of grain. Regular control of grain quality in the Khmelnytsky region is subject to constant control with the help of laboratory tests. Grain produced in the region, as a rule, meets the requirements of state standards of Ukraine and international standards.Thus, іn order to ensure the high quality of grain indicators, it is necessary to introduce a system of ensuring and controlling the quality of raw materials and products of the agricultural industry at a sufficiently high level. For these reasons, it is expedient at the department of chemistry and chemical engineering within the educational component "Quality of raw materials and products of chemical technologies" ЕР of the master's level to participate, among other tasks, in the examination and quality control of cereals. This applies both to the study of the regulatory framework for grain quality assurance and control, and to laboratory research methods, most of which are possible with the available material and technical support of the Department of Chemistry and Chemical Engineering.
Keywords: agricultural products; quality of agricultural products; grain; product quality control